2020
DOI: 10.21203/rs.3.rs-84108/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of training podiatrists to use imagery-based motivational interviewing to improve self-care for people with diabetes-related foot disease: A mixed-methods pilot study

Abstract: Background Self-care in diabetic foot disease (DFD) is challenging and can contribute to poor outcomes. Motivational Interviewing (MI) engages people in self-care and integrating imagery may further improve its outcomes. No previous studies have trained podiatrists in using MI to address DFD self-care. This was the first study on training podiatrists to conduct imagery-based motivational interviewing (MI) when treating people with diabetes-related foot disease (DFD), and to examine impacts on MI related skill… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The qualitative responses suggested this would be highly valued. With 8 h of training provided in the current study, half of the median 16 h found in a systematic review [ 34 ], more training may indeed be needed for lasting positive effects on practice. In particular, further group discussion of difficulties experienced in applying MI is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative responses suggested this would be highly valued. With 8 h of training provided in the current study, half of the median 16 h found in a systematic review [ 34 ], more training may indeed be needed for lasting positive effects on practice. In particular, further group discussion of difficulties experienced in applying MI is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Effective application of imagery-based MI requires that practitioners are sufficiently trained to apply it routinely with high fidelity in their work [ 19 ]. MI skills can be acquired by nurses or general practitioners who care for people with diabetes, albeit to varying success [ 22 , 29 – 33 ], depending in part on the length of MI training and availability of supervision [ 34 ]. However, training podiatrists in using MI to address DFD self-care has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%